2008
DOI: 10.1086/527489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjuvants on the Safety and Immunogenicity of an Avian Influenza H5N1 Vaccine in Adults

Abstract: ClincalTrials.gov identifier: http://www.clinicaltrials.gov/ct2/show/NCT00280033?term= NCT00280033&rank=1 NCT00280033 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
108
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(121 citation statements)
references
References 13 publications
13
108
0
Order By: Relevance
“…The results from the first clinical trials of unadjuvanted H5N1 vaccines were disappointing in terms of immunogenicity (1). However, substantial improvements have been seen in trials with the adjuvanted formulations specifically using the new-generation oil-in-water emulsion-based adjuvants, which have induced significantly higher antibody responses to low antigen-content vaccines (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the first clinical trials of unadjuvanted H5N1 vaccines were disappointing in terms of immunogenicity (1). However, substantial improvements have been seen in trials with the adjuvanted formulations specifically using the new-generation oil-in-water emulsion-based adjuvants, which have induced significantly higher antibody responses to low antigen-content vaccines (2,3).…”
mentioning
confidence: 99%
“…MF59 has been tested with H5 and H9 influenza vaccines and showed promising results; an ability to potentiate and increase the breadth of the immune response induced by low-antigen-content vaccines (2,5). It has been shown that alum and MF59 induce the secretion of a range of cytokines associated with recruitment of innate immune cells to the injection site (6).…”
mentioning
confidence: 99%
“…The challenge posed by poorly immunogenic and antigenically diverse avian influenza viruses (e.g. H5N1) led to a number of developments in adjuvents that provide enhanced immunogenicity as well as broad cross-clade protection and allow antigen-sparing strategies [63,64]. The unpredictable nature of pandemics implies monitoring and preparedness to immunize against a range of potential pandemic candidates, knowing fully well that predicting the vagaries of influenza virus behavior is well-nigh impossible, as we saw with the unexpected emergence of H1N1v as a pandemic.…”
Section: Challenges For Immunologistsmentioning
confidence: 99%
“…The MF59 oil‐in‐water emulsion adjuvant used in Novartis’ licensed seasonal influenza vaccine for the elderly, Fluad ® , has been shown to increase immune responses to H5N1 after both homologous vaccination as well as after heterologous vaccination with a non‐pathogenic H5N3 virus‐derived vaccine 50 , 51 . Another proprietary oil‐in‐water emulsion‐based adjuvant has been developed by GlaxoSmithKline Biologicals (GSK) and has been tested in an H5N1 prototype vaccine formulation 52 .…”
Section: Adjuvanted Pandemic Influenza Vaccinesmentioning
confidence: 99%